The Gender Ideology of State Ibuism and Women’s Roles in Care Practices at the Rawa Panjang Waste Bank, Bojonggede, Bogor - Purnamasari, Marini (UI Scholars Hub, 2024)
This article examines women's involvement in community-based waste management through the Waste Bank program. It argues that women’s participation in managing waste banks reflects the state’s gender ideology, which reinforces the reproduction of female labor and caregiving roles within society. Applying Suryakusuma’s (2011) concept of state ibuism, this study explores women’s roles in the Waste Bank program in Rawa Panjang, Citayam, Bogor Regency. Employing a qualitative approach, it utilizes methods such as observation, focus group discussions (FGDs), photoelicitation interviews, and in-depth interviews. The findings indicate that the Waste Bank program in Rawa Panjang serves as a contemporary manifestation of state ibuism within the broader context of development. Women involved in managing waste banks engage in caregiving labor related to household and community waste management, placing them in vulnerable positions due to exposure to waste while receiving inadequate compensation. This dynamic exacerbates their reproductive labor burden, underscoring the gendered inequalities embedded in environmental management responsibilities.